2022
DOI: 10.1126/sciadv.abp9929
|View full text |Cite
|
Sign up to set email alerts
|

Highly multiplexed, label-free proteoform imaging of tissues by individual ion mass spectrometry

Abstract: Imaging of proteoforms in human tissues is hindered by low molecular specificity and limited proteome coverage. Here, we introduce proteoform imaging mass spectrometry (PiMS), which increases the size limit for proteoform detection and identification by fourfold compared to reported methods and reveals tissue localization of proteoforms at <80-μm spatial resolution. PiMS advances proteoform imaging by combining ambient nanospray desorption electrospray ionization with ion detection using individual ion mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…Direct fragmentation of proteoforms in situ during MSI have been demonstrated recently as the TDP methods and instruments improved. (Garza et al, 2018;Griffiths et al, 2020;Su et al, 2022;Yang et al, 2022) Herein, we have shown the assignment of several high abundance proteins and a few cysteine-rich peptides. Fully automated peak assignment for proteoform analysis is being actively developed.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Direct fragmentation of proteoforms in situ during MSI have been demonstrated recently as the TDP methods and instruments improved. (Garza et al, 2018;Griffiths et al, 2020;Su et al, 2022;Yang et al, 2022) Herein, we have shown the assignment of several high abundance proteins and a few cysteine-rich peptides. Fully automated peak assignment for proteoform analysis is being actively developed.…”
Section: Discussionmentioning
confidence: 62%
“…(Hollas et al, 2021;Smith et al, 2021;Melani et al, 2022) The limitations of intact protein sample complexity, low sensitivity, and sequence coverage against large proteins remain, but are being addressed with new experimental technologies including solution-phase separation and enrichment (Melby et al, 2021), ion mobility (Fulcher et al, 2021;Gerbasi et al, 2021), proton transfer reaction (Huguet et al, 2019;Ugrin et al, 2019) and charge detection mass spectrometry (Harper et al, 2019;Kafader et al, 2020;Todd et al, 2020;Worner et al, 2020;Su et al, 2022). Notably, charge detection-based method expanded the measurable proteoforms into 70 kDa range in a recent TDP tissue imaging study by nanospray desorption electrospray ionization (nanoDESI), (Su et al, 2022), highlighting the potential for easier access of high mass proteoforms. Our TDP results on soybean root nodule demonstrate the ways in which TDP can already make significant contributions in studying the proteome <25 kDa despite technologies not yet being mature enough for accessing the full proteome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al. [ 260 ] developed a proteoform imaging mass spectrometry method by coupling nano‐DESI MSI with individual ion mass spectrometry (I 2 MS). [ 261 ] Using Orbitrap‐based charge detection I 2 MS and computational signal transformation, 169 proteoforms have been identified in every pixel and proteoform‐selective imaging data were obtained with a spatial resolution of 80 µm.…”
Section: Computational Methods For Msi Experimentsmentioning
confidence: 99%
“…While these technologies are highly effective and can provide single-cell level or better spatial resolution, protein coverage is limited by the availability of reliable antibodies and the multiplexing limit of the labels. Imaging mass spectrometry (MALDI, Laser Ablation) is also a powerful tool for protein mapping that does not depend on antibody recognition; but due to the direct coupling to the mass spectrometer, these techniques are limited in their dynamic range and accuracy of quantitation [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%